The Implementation of Islamic Corporate Governance (ICG) on Sharia Banking in Indonesia - Nova Rini (TIJAB (The International Journal of Applied Business), 2018)
In 2001, a financial institution in Turkey went bankrupt. The financial institution is "Ihlas Finance House". The cause of the bankruptcy of financial institutions according to Islamic finance economists is as a result of weaknesses in the internal and external mechanisms of corporate governance. The purpose of writing this article is to find out how the implementation of Islamic Corporate Governance in Islamic Banking. The method used in this article to answer the research question is a literature study. The results of this study indicate that Islamic banking financial institutions in Indonesia have not fully implemented Islamic Corporate Governance (ICG). The implementation of Islamic Corporate Governance (ICG) that has not been fully implemented is sharia compliance (syari'ah compliance). Sharia compliance in Islamic bank financial products. Conclusion of this article: 1. Implementation of Islamic Corporate Governance (ICG) in Islamic banking is accommodated in the Sharia Banking Law and Bank Indonesia Regulations; 2. Islamic Corporate Government (ICG) can be seen from the establishment of Sharia Supervisory and Sharia Compliance Board in Islamic banking; and 3. Islamic banking in Indonesia does not yet fully implement Islamic Corporate Governance (ICG) in sharia compliance for Islamic financial products.